Composite Stock Price Index and Currency Exchange Rates of 4 Countries in Southeast Asia after Covid-19 - Satria, Dias (Jurnal Keuangan dan Perbankan, 2023)
The Covid-19 pandemic has caused a social and economic crisis in every country, leading to economic shocks that can be observed through the movement of the Composite Stock Price Index (CSPI) and Exchange Rate (ER). To determine the economic conditions of four Southeast Asian countries, this study aims to examine their exchange rates and CSPI. However, the pandemic has made economic factors unpredictable since every country has responded differently to it. The research focuses on Indonesia, Malaysia, Singapore, and Thailand from 2013 to 2022, using Vector Autoregression Model (VAR) modeling to analyze the relationship between the variables and their movements. The study found that exchange rate changes in the previous two periods significantly influence exchange rate changes in the four countries, and changes in exchange rates and JCI in Indonesia and Thailand affect subsequent changes with a longer time horizon. The study's results emphasize the importance of tailoring economic management based on each country's unique economic characteristics and taking measures to stabilize the exchange rate and CSPI movement. Policymakers and investors should consider the findings of this study to make informed economic decisions, especially in anticipating the impact of sudden exchange rate fluctuations and their potential long-term consequences.